Early intervention in psoriasis and immune-mediated inflammatory diseases: A hypothesis paper. (April 2015) - Girolomoni, G.; Griffiths, C. E. M.; Krueger, J.; Nestle, F. O.; Nicolas, J-F.; Prinz, J. C.; Puig, L.; Ståhle, M.; van de Kerkhof, P. C. M.; Allez, M.; Emery, P.; Paul, C.
Abstract Psoriasis is an immune-mediated inflammatory disease (IMID) which may have a major impact on a patient's life, especially when the disease is moderate to severe. There is evidence that treatment of psoriasis during the first years is conservative and frequently based on topical agents which rarely clear lesions. Treatment with systemic agents including biologics is often undertaken only when topical agents have proved unsuitable, even in patients with moderate to severe disease. However, there is evidence that in other IMIDs (rheumatoid arthritis and Crohn's disease), targeted systemic treatment given early in the treatment pathway may improve long-term patient outcomes. We hypothesize that a patient-centered therapeutic approach, undertaken early in the psoriasis treatment pathway ("early intervention") with the goal of complete clearance, may improve control of cutaneous symptoms and may also modify disease course and burden. Critical points to address when designing an early intervention study would include: the definition of psoriasis disease activity; patient selection; intervention selection; and dosing strategies.